2017
DOI: 10.1002/bjs.10602
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide outcomes in patients undergoing surgical exploration without resection for pancreatic cancer

Abstract: Exploration and resection rates increased, but one-third of patients who had surgical exploration for pancreatic cancer did not undergo resection. Non-resectional surgery doubled the 30-day mortality rate compared with that in patients undergoing tumour resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Our study revealed that the NRR did not decrease during the last 2 decades among patients with PDAC entering the operating room for an intention-to-cure pancreatectomy. The observed overall NRR of 24.5% was consistent with those of previously reported series among patients diagnosed with PDAC [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our study revealed that the NRR did not decrease during the last 2 decades among patients with PDAC entering the operating room for an intention-to-cure pancreatectomy. The observed overall NRR of 24.5% was consistent with those of previously reported series among patients diagnosed with PDAC [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…The higher mortality rates among the unresectable group in comparison to the resectable group were expected. A high 30-day mortality was also seen in a cohort including only pancreatic cancer patients 12 . Having an unresectable tumor indicates a more disseminated disease, which should impact the expected survival negatively.…”
Section: Discussionmentioning
confidence: 82%
“…Among patients who underwent surgical exploration, the proportion of patients with tumor resection did not increase. In an article including only pancreatic cancer patients, an increased resection rate was seen comparing 2009 and 2013, but still almost one-third of patients with surgical exploration for pancreatic cancer did not undergo resection 12 . During the last years, a centralization of pancreatic surgery has been completed in many countries and the sensitivity of preoperative imaging has been improving 9 , 12 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies confirm that compliance with only a few elements of those protocols results in fewer benefits for outcome improvement. CHO loading, early nutrition support and avoiding fluid overload are key factors contributing to the decreased length of hospital stay, number of postoperative complications and readmission rates in abdominal surgery [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%